STUDI KUALITAS PERAIRAN PADA KEGIATAN BUDIDAYA TIRAM MUTIARA (Pinctada maxima) DI KECAMATAN GEROKGAK, KABUPATEN BULELENG, BALI - SUPII, APRI. I.; Arthana, I W (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
The purpose of this study were to know the effect of pearl oyster culture activities to the water quality (physical, chemical, biological parameters), and the sediment of culture site, waters quality status of pearl oyster culture site as well. The research was done at 10 stations, which were 9 stations located around pearl oyster culture site, and 1 station located at out of pearl oyster culture site (as control). Results showed that the sources of pollution were from pearl oyster feces and biofouling produced from cleaning of pocket and its shell. An in organic matter of the feces produced (50.52-78.75 %) was higher than the organic matter (21.25-49.48 %). The amount of biofoulling trash increased with the size and dominated by organic matter. Sea water quality observed was under sea water quality standard of marine organism (aquaculture) decided by government, except phosphate. Twenty four species of plankton collected, consist of 4 phylum, that were Bacillarophyta (diatom), Protozoa, Arthropoda, and Mollusca. Plankton Diversity Index showed the level of low to high pollution condition indicated ecological suppression and decreasing of waters quality. The amount of total bacteria and Vibrio spp. at all stations were normal, that was less than 106 cfu/ml. Integrated physical, chemical and biological parameters assessment found that pollution index was 2-3, mean of low pollution. Result of Cluster assessment indicate that there was real characteristic differentiation between first group (1-9) and second group (control). First group was around the pearl oyster culture waters, and second group was out of the pearl oyster culture waters. So the pearl oyster culture activities affected the waters quality.
Keywords: Pearl Oyster, Water Quality of Marine, Buleleng.